Double pyramid technique of transoral laser partial laryngectomy for radiorecurrent laryngeal cancer. Issue 1 (28th November 2018) - Misirovs, Rasads; Gartner, Isabel; Manickavasagam, Jaiganesh
Abstract : Management of recurrent head and neck cancer is challenging. Surgical treatments for residual or radiorecurrent laryngeal cancer include total laryngectomy, open partial laryngectomy and transoral laser microsurgery (TLM). TLM has been shown to achieve good oncological and functional outcomes in radiorecurrent laryngeal cancer. We describe a case of a patient with radiorecurrent T2 (rT2) with impaired vocal cord mobility laryngeal cancer who underwent transoral laser partial laryngectomy using our proposed double pyramid technique. It encompasses two steps: resection of the superior and inferior pyramids. Full resection is achieved by staying close to the thyroid and cricoid cartilages. In this technique, the dissection principle is to remove anterior commissure in two pyramid fashions without having to actually follow the tumour. This method is easy and simple to master. Two years postoperatively, the patient has no signs of recurrence and is able to use her voice and has full swallowing ability.